Safety of Early Carotid Artery Stenting after Systemic Thrombolysis: A Single Center Experience - Fabrizio Sallustio; Giacomo Koch; Alessandro Rocco; Costanza Rossi; Enrico Pampana; Roberto Gandini; Alessandro Meschini; Marina Diomedi; Paolo Stanzione; Silvia Di Legge (Stroke Research and Treatment)
Background. Patients with acute ischemic stroke due to internal carotid artery (ICA) disease are at high risk of early stroke recurrence. A combination of IV thrombolysis and early carotid artery stenting (CAS) may result in more effective secondary stroke prevention. Objective. We tested safety and durability of early CAS following IV thrombolysis in stroke patients with residual stenosis in the symptomatic ICA. Methods. Of consecutive patients treated with IV rtPA, those with residual ICA stenosis ≥70% or <70% with an ulcerated plaque underwent early CAS (>24 hours). The protocol included pre-rtPA MRI and MR angiography, and post-rtPA carotid ultrasound and CT angiography. Stroke severity was assessed by the NIH Stroke Scale (NIHSS). Three- and twelve-month stent patency was assessed by ultrasound. Twelve-month functional outcome was assessed by the modified Rankin Scale (mRS). Results. Of 145 consecutive IV rtPA-treated patients, 6 (4%) underwent early CAS. Median age was 76 (range 67–78) years, median NIHSS at stroke onset was 12 (range 9–16) and 7 (range 7-8) before CAS. Median onset-to-CAS time was 48 (range 30–94) hours. A single self-expandable stent was implanted to cover the entire lesion in all patients. The procedure was uneventful in all patients. After 12 months, all patients had stent patency, and the functional outcome was favourable (mRS ≤ 2) in all but 1 patient experiencing a recurrent stroke for new-onset atrial fibrillation. Conclusion. This small case series of a single centre suggests that early CAS may be considered a safe alternative to CEA after IV rtPA administration in selected patients at high risk of stroke recurrence.